1997
DOI: 10.1038/bjc.1997.178
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic pneumonia syndrome after high-dose chemotherapy for relapsed Hodgkin's disease

Abstract: (Goldstone et al, 1993). Rates of morbidity and mortality have improved with better supportive measures and administration of HDC at an earlier phase in the course of the disease, but procedure-related mortality remains in the region of 10-20% in most published series using autologous bone marrow transplantation (ABMT) Jones et al, 1990;Reece et al, 1991;Bierman et al, 1993). Approximately 50% of these fatalities will be as a consequence of idiopathic pneumonia syndrome (IPS). This presents with dyspnoea, pulm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 17 publications
0
30
0
1
Order By: Relevance
“…5 However, 23 out of 26 patients who developed idiopathic pneumonia syndrome following BCNU-based high-dose chemotherapy with autologous bone marrow transplantation (ABMT) for relapsed Hodgkin's disease, experienced symptoms during the first 6 months post-treatment (with the remaining three patients diagnosed between 6 and 12 months post-chemotherapy). 6 In another report, 3 26 women with breast cancer, who underwent ABMT after BCNU-based conditioning, developed pulmonary symptoms with a median onset of 10.3 weeks (range 2.4-16.6 weeks). Finally, in a retrospective study of 10 women with breast cancer and biopsy-proven pulmonary toxicity after high-dose BCNU, all became symptomatic at a mean time of 48 ± 14 days (range, 21-62 days) after the initiation of high-dose treatment.…”
Section: Discussionmentioning
confidence: 99%
“…5 However, 23 out of 26 patients who developed idiopathic pneumonia syndrome following BCNU-based high-dose chemotherapy with autologous bone marrow transplantation (ABMT) for relapsed Hodgkin's disease, experienced symptoms during the first 6 months post-treatment (with the remaining three patients diagnosed between 6 and 12 months post-chemotherapy). 6 In another report, 3 26 women with breast cancer, who underwent ABMT after BCNU-based conditioning, developed pulmonary symptoms with a median onset of 10.3 weeks (range 2.4-16.6 weeks). Finally, in a retrospective study of 10 women with breast cancer and biopsy-proven pulmonary toxicity after high-dose BCNU, all became symptomatic at a mean time of 48 ± 14 days (range, 21-62 days) after the initiation of high-dose treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The higher incidence of major NIPC observed in patients treated with BCV compared with those who received BEM (35% vs 12%) supports the hypothesis that CY may augment the detrimental effect of BCNU on the lungs; comparable results were observed in breast cancer patients receiving BCNU associated with CY and cisplatin. 3 In a dose toxicity study of 72 patients receiving a modified BEM regimen Ager et al 5 observed that BCNU given at the dose of 600 mg/m 2 to seven patients (five lymphomas, one ANLL, one MM), was associated with an unacceptable incidence of lung toxicity (42%); Rubio et al 4 reported idiopathic pneumonia in 28% of patients with relapsed HD receiving a BEM regimen, while in our study patients receiving BEM had minimal lung toxicity; they all had MM.…”
Section: Discussionmentioning
confidence: 99%
“…In some reports late administration of steroids may explain the high incidence of fatal NIPC. 4,5 Prophylactic use of steroids concurrent with BCNU to prevent pulmonary toxicity or progression of toxicity is still debatable: 6,7,24 its use should be tested in a randomised trial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Some risk factors, such as history of irradiation to lung, cigarette smoking, female gender and a dosage greater than 475 mg/m 2 , are known to be associated with BCNU-related pulmonary injury. 4,5 However, the pathogenetic mechanism of BCNU-associated pulmonary fibrosis has never been studied.…”
Section: Cox-2mentioning
confidence: 99%